2006
DOI: 10.1007/s10709-005-5702-z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogeny of black flies (Diptera: Simuliidae) from Thailand, using ITS2 rDNA

Abstract: The sequences of the second internal transcribed spacer (ITS2) of ribosomal DNA (rDNA) were determined for 40 black fly species from Thailand, belonging to 4 subgenera of the genus Simulium, namely Gomphostilbia (12 species), Nevermannia (5 species), Montisimulium (1 species), Simulium sensu stricto (21 species), and an unknown subgenus with one species (Simulium baimaii). The length of the ITS2 ranged from 247 to 308 bp. All black fly species had high AT content, ranging from 71 to 83.8%. Intraindividual vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 69 publications
1
33
1
1
Order By: Relevance
“…The analyzed populations do not differ in proportion of nucleotide bases, where A and T dominate with an average of 65.86% which is a phenomenon typical for arthropods (Hebert et al 2003) but also recognized in blackflies (Xiong & Kocher 1991;Morales-Hojas et al 2002b;Thanwisai et al 2006;Rivera & Currie 2009). This percentage is similar to that found in the same gene in Simulium reptans Linnaeus, 1758, Simulium galeratum Edwards, 1920 (Day et al 2008) and many North American species Finn & Adler 2006;Rivera & Currie 2009).…”
Section: Discussion: Isolation Versus Continuitymentioning
confidence: 83%
“…The analyzed populations do not differ in proportion of nucleotide bases, where A and T dominate with an average of 65.86% which is a phenomenon typical for arthropods (Hebert et al 2003) but also recognized in blackflies (Xiong & Kocher 1991;Morales-Hojas et al 2002b;Thanwisai et al 2006;Rivera & Currie 2009). This percentage is similar to that found in the same gene in Simulium reptans Linnaeus, 1758, Simulium galeratum Edwards, 1920 (Day et al 2008) and many North American species Finn & Adler 2006;Rivera & Currie 2009).…”
Section: Discussion: Isolation Versus Continuitymentioning
confidence: 83%
“…Analyses of the sequences (Alvarez and Wendel 2003;Webster et al 2004;Marrelli et al 2006;Thanwisai et al 2006;Ben-David et al 2007) showed that such a method could be potentially used to identify astigmatid mites with similar morphological characteristics. When the mites were cloned, as in B. tropicalis described here, few or no differences were observed in their ITS2 regions.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial DNA (mtDNA) has been widely used in systematic and many universal PCR primers are available for genes like COI and CytB (Avise, 2004). The ITS2 region is easy to amplify and have been used in previous phylogenetic studies of Diptera (Hwang, 2007;Thanwisai et al, 2006). This work explores congruence and information content within the different molecular datasets analysed using probabilistic methods of phylogenetic reconstruction.…”
Section: Introductionmentioning
confidence: 99%